Overexpression of PpSnRK1α in Tomato Promotes Fruit Ripening by Enhancing RIPENING INHIBITOR Regulation Pathway - Yu, Wen; Peng, Futian; Xiao, Yuansong; Wang, Guifang; Luo, Jingjing (Frontiers in Plant Science, 2018)
As a conserved kinase complex, sucrose non-fermenting-1-related protein kinase 1 (SnRK1) is a major regulator of plant growth and development. In our previous study, overexpression of MhSnRK1 in tomato (Solanum lycopersicum L.) modified fruit maturation: the transgenic fruit ripened earlier than the wild type. However, the mechanism by which fruit maturation is regulated by SnRK1 is not clear; therefore, the test materials used were the transgenic tomato lines (OE-1, OE-3, and OE-4) overexpressing the coding gene of peach (Prunus persica (L.) Batsch) SNF1-related kinase α subunit (PpSnRK1α). The activity of SnRK1 kinase in transgenic tomato lines OE-1, OE-3, and OE-4 was higher than that in the wild type at different periods of fruit development; in the pink coloring period the SnRK1 kinase activity increased the most, with 23.5%, 28.8%, and 21.4% increases, respectively. The content of starch and soluble sugars in red ripe transgenic fruit significantly increased, while the soluble protein and titratable acid content decreased significantly. We also found that the tomatoes overexpressing PpSnRK1α matured approximately 10 days earlier than the wild type. Moreover, the yeast-two-hybrid assay showed that PpSnRK1α interacted with the MADS-box transcription factor SIRIN, which acts as an essential regulator of tomato fruit ripening. The BiFC technology further validated the location of the PpSnRK1α interaction sites within the nucleus. The quantitative real-time PCR analysis showed that RIN expression was up-regulated by PpSnRK1α overexpression; the expression of RIN-targeted transcription factor genes NOR and FUL1 increased during different stages of fruit development. The expression of key genes, ACS2, ACS4, and E8, in ethylene synthesis also changed accordingly, and the ethylene emitted by the red ripe fruit increased by 36.1% to 43.9% compared with the wild type. These results suggest that PpSnRK1α interacts with SIRIN, increasing the expression of RIN, thereby regulating the expression of downstream ripening-related genes, finally promoting fruit ripening.